Prevalence and Risk of Violent Ideation and Behavior in Serious Mental Illnesses: An Analysis of 63,572 Patient Records - Roché, Matthew W. (Journal of interpersonal violence, 2021)
Research has consistently demonstrated that people diagnosed with serious mental illness (SMI) are at increased risk for violent ideation and behavior (VIB) and that this is especially the case for SMI patients with comorbid substance use disorders (SUD). Despite this, what is still largely unknown is the relative prevalence of VIB across diagnostic categories, whether the rates of VIB in SMI groups exceed the rates observed in people with SUD only, and which demographic factors increase the likelihood of VIB under different circumstances for people with SMI. To address these questions, we analyzed the intake records of 63,572 patients diagnosed with SMIs (i.e., schizoaffective disorder, schizophrenia, bipolar disorder, and unipolar depression), substance use disorders, and non-SMI psychiatric disorders. Raw prevalence rates for a combined metric of VIB were established and compared for each group, and a series of logistic regression analyses were performed to estimate how various demographic factors influenced the likelihood of VIB endorsement in each study group. Our results revealed that (a) patients with SMI conditions had higher rates of VIB than both patients with non-SMI psychopathology and those with substance use disorders only; (b) patients with SMI and comorbid substance use pathology were responsible for the majority of VIB within each SMI condition; and (c) men with SMI conditions had higher prevalence rates of VIB than females. In addition, we found that for every SMI diagnosis, comorbid substance use disorders and younger age were related to greater risk for VIB, and where race and gender were found to significantly alter the likelihood of VIB endorsement, African American status and female gender were independently related to greater risk. The implications of these findings and directions for future research are discussed.